PENGADAAN USAHA WEDANG UWUH DENGAN PEMBERDAYAAN IBU RUMAH TANGGA SEBAGAI PENGENTAS KEMISKINAN - Hartati, Anies Siti; Suryaningsum, Sri (Jurnal Manajemen Dayasaing, 2019)
This is an action research conducted with empowerment effort which is addressed to housewife in Dusun Dukuh Imogiri Bantul. The data collection used in this research is observation method, document and interview. This study aims to improve the knowledge and skills of housewives. Efforts to empower done by considering the surrounding natural resources that have not been optimally utilized herbs that thrive in the yard of the community. The empowerment effort is done by training activity, that is the training of wedang uwuh making and marketing training of wedang uwuh. In addition to improving knowledge and skills as well as providing alternative productive activities, this training is also an effort to eradicate poverty because the sale of wedang uwuh can improve the economy of Dusun Dukuh.